Analysis of Polyhouse Parameter to improve Agriculture efficiency Using PLC and SCADA - Dnyaneshwar D. Saruk; Mandar K. Mokal; Suraj H. More; Darshan J. Mokal; Sharvari Sane (International Journal of Advanced Control and System Engineering, 2024)
Climate change brought on by pollution, global warming, etc. has impacted the agriculture sector's yield recently. The fact that our farmers continue to use conventional practices is another factor. On the other side, one of the primary problems this research focuses on employing green technology, namely poly home farming, is the depletion of resources like land and water. Therefore, the study in this paper focuses on applying end-to-end solutions to control temperature, humidity, soil moisture, CO2, light intensity, rainfall, tank level, etc. in order to improve agricultural productivity. Additionally, this job is targeted. Regarding the collection of rainfall. It has been noted that yield has increased with improved quality and efficient use of resources.
Keywords: Agriculture; Humidity; PLC; Polyhouse; SCADA; sensors; temperature